FEDERALISM IN IRAQ: ASSESSMENT - Hanish, Shak (PEOPLE: International Journal of Social Sciences, 2015)
Since 2003, there is a debate about dividing Iraq into three states or regions in accordance with its ethnicity and religious sects. There are groups supporting unity of Iraq to keep it a united country and to continue the process of rebuilding a new Iraq, a process that started after the First World War. Still, there are those who think Iraq is a failure state and the solution is to divide it into three entities to calm down ethnic and sectarian division. In this paper, I will examine the two main points of view and assess them to see which solution will suit better Iraq, or which solution is the least harmful, in order to keep peace and stability in this war-torn country. At issue will be centralism in Iraq and its evolution to federalism. I will see if confederation is another solution to the problem. In addition, the paper will look at the struggle of the Kurdish people for their national rights and will assess splitting Iraq into two states as a valuable solution. Finally, I will conclude my paper by evaluating the issue of dividing Iraq and hopefully providing possible solutions.